Mosaic 1 : - Hanreddy, Jami (Tổng hợp Thành phố Hồ Chí Minh : McGraw-Hill, 2009)
Language proficiencies are articulated across five ability levels (beginning through advanced) within each of the four language skill strands. Chapter themes articulate across the four skill strands to systematically recycle content, vocabulary, and grammar. This is the low intermediate to intermediate level Grammar student book.